Characterising heterogeneity in the use of different cannabis products: latent class analysis with 55 000 people who use cannabis and associations with severity of cannabis dependence. Issue 14 (13th October 2020) - Craft, Sam; Winstock, Adam; Ferris, Jason; Mackie, Clare; Lynskey, Michael T.; Freeman, Tom P.
Abstract: Background: As new cannabis products and administration methods proliferate, patterns of use are becoming increasingly heterogeneous. However, few studies have explored different profiles of cannabis use and their association with problematic use. Methods: Latent class analysis (LCA) was used to identify subgroups of past-year cannabis users endorsing distinct patterns of use from a large international sample ( n = 55 240). Past-12-months use of six different cannabis types (sinsemilla, herbal, hashish, concentrates, kief, edibles) were used as latent class indicators. Participants also reported the frequency and amount of cannabis used, whether they had ever received a mental health disorder diagnosis and their cannabis dependence severity via the Severity of Dependence Scale (SDS). Results: LCA identified seven distinct classes of cannabis use, characterised by high probabilities of using: sinsemilla & herbal (30.3% of the sample); sinsemilla, herbal & hashish (20.4%); herbal (18.4%); hashish & herbal (18.8%); all types (5.7%); edibles & herbal (4.6%) and concentrates & sinsemilla (1.7%). Relative to the herbal class, classes characterised by sinsemilla and/or hashish use had increased dependence severity. By contrast, the classes characterised by concentrates use did not show strong associations with cannabis dependence but reported greater rates of ever receiving a mental health disorder diagnosis. Conclusions: The identification of these distinct classes underscores heterogeneity among cannabis use behaviours and provides novel insight into their different associations with addiction and mental health.